(untitled) (Web of Teachers: Inderscience Research, 2026)
This article discusses the theoretical and practical aspects of the formation of listening skills in the process of teaching a foreign language. The role of listening in the system of speech activity, its relationship with other types of speech activity, as well as methods for developing this skill in students are analyzed. Particular attention is paid to listening difficulties (phonetic, grammatical and lexical) and ways to overcome them.